Anxiety level of pregnant women before pregnancy termination for fetal abnormality - Geylani, Merve; Doğan, Sibel; Atayoğlu, Ali Timuçin (Kare Yayıncılık, 2020)
Objectives: Holistic approaches in health care services consider all aspects of individuality. This research was conducted as a descriptive study to evaluate the anxiety level of pregnant women before the termination of the pregnancy for fetal abnormalities. Methods: This descriptive and cross-sectional study comprised pregnant women who were admitted to the prenatal diagnosis and treatment unit before pregnancy termination for a severe fetal abnormality. As the data collection tool, a questionnaire containing the descriptive and obstetric characteristics of the pregnant women, their feelings and thoughts about pregnancy and the State-Trait Anxiety Inventory were used in this research. In the evaluation of the research data, percentage values, arithmetic mean, standard deviation, median, minimum and maximum values were given as descriptive statistics of the data. Results: This study consisted of 83 pregnant women. The findings showed that 49 (59.0%) of pregnant women experienced sadness, and 41 (49.4%) needed psychological support before the termination of pregnancy. The mean State-Trait Anxiety Inventory score of the pregnant women was 60.7±11.6, and that they experienced high levels of anxiety. Conclusion: The findings suggest that pregnant women before the termination of pregnancy for severe fetal abnormalities should be evaluated and supported psychosocially.
Keywords: Anxiety; Congenital Abnormalities; Fetus; Holistic Health; Pregnancy